BECOMING A TEACHER: HOW TO RECOGNIZE THE SELF AS A LEADER IS A CLASSROOM - Zydziunaite, Vilma; Kaminskiene, Lina; Jurgile, Vaida; Ponomarenko, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The notion of ‘teacher leader in a classroom’ recently has been shifted. In the past, teacher leadership in a classroom was limited to didactics and expertise. Teachers have long served as ‘executors’, ‘executants’, not ‘leaders’ who are capable to manage the change and co-creation of knowledge within the interaction with students in a classroom. The aim of the study is to provide the descriptive analysis on contemporary research-based development regarding teacher leadership with the focus on concepts such as ‘becoming a teacher’, ‘professionalism of a teacher’, ‘co-creation’ and ‘teacher leadership’. Methods. The study is based on descriptive theoretical analysis. Conclusion. Becoming a teacher is the continuous process and means accepting the chal-lenge of imparting knowledge and guidance and approaching a high degree of ambivalence as it requires great diligence on the part of the teacher to be able to carry out her / his pro-fessional responsibilities. Co-creation is inseparable part of both - becoming a teacher and being a teacher leader as it helps to support the positive teaching-learning relationships and create the effective learning environments. Teacher leadership in a classroom is impossible to implement without self- recognition, which means in teaching practices teacher’s self-awareness.